A Case of Nodular Chest Shadows - Mandal, Pijush Kanti; Dey, Arpan Kumar; Pramanik, Subhraprakash; Dasgupta, Somenath; Momin, Tanmoy W (Asian Journal of Medical Sciences, 2013)
Pulmonary Tuberculosis is still very common in India as well as in other developing countries. The lesions are usually woolly, ill-defined opacities and may be associated with cavities. Multiple nodular discrete bilateral opacities affecting the lungs from base to apex, more in the lower zones is unusual in Pulmonary Tuberculosis. We report a case of a 55 year old male with bilateral multiple nodular opacities of varying sizes as evident on chest radiography presented with dry cough and one episode of haemoptysis, which initially raised a possibility of lung metastasis. CT guided FNAB from left lung lesion showed chronic granulomatous lesion likely to be of Tubercular aetiology. Sputum for Acid Fast Bacilli (AFB) was negative but the culture for AFB was positive and the patient responded to treatment with Antituberculardrugs (ATDs). DOI: http://dx.doi.org/10.3126/ajms.v5i2.8297 Asian Journal of Medical Science, Volume-5(2) 2014: 130-133